Analisis Bibliometrik Klasifikasi Biaya Dalam Konteks Produksi Serta Perannya Terhadap Optimalisasi Goals Perusahaan (Literature Riview) - Muammar Khaddafi; Nurhayati Nurhayati; Yola Deviani; Suci Ananda; Nugra Kurnianto (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2024)
This article analyzes the impact of production costs and their classification on company objectives through a literature study using descriptive qualitative methods. Through a search on Google Scholar with the keywords